Competitive Organizational Behavior: Toward an Organizationally-Based Theory of Competitive Advantage - Barney, Jay B.; Zajac, Edward J. (Strategic Management Journal, 1994)
Strategy implementation scholars have traditionally focused their attention on behavioral and social phenomenc in a firm that enable it to both choose and implement its strategies. Unfortunately, some of this work has assumed that it is possible to study strategy implementation independent of the content of a firm's strategies, and independent of the particular competitive context within which a firm operates. Recent developments in the resource-based view of the firm reaffirm the importance of studying the strategic consequences of behavioral and social phenomena within a firm, but suggest that separating this work from the content of strategy, or from the competitive context of a firm, is inappropriate. The papers in this special issue focus on important behavioral and social phenomena in a firm (e.g., organizational behavior), but do so in an explicit competitive context (e.g., competitive organizational behavior).